Professional Characteristics of Canadian Counsellors: Results of a National Survey - Gazzola, Nicola; Smith, J. David; Kearney, M. Kate; King-Andrews, Heather L. (Canadian Journal of Counselling and Psychotherapy, 2010)
With statutory regulation of mental health professions clearly at the forefront in many Canadian jurisdictions, counselling appears to be experiencing internal tensions regarding its vision and direction. The goal of this study was to collect data directly from Canadian counsellors to more clearly define the current practices of counselling in Canada. We developed a web-based survey and invited members of the Canadian Counselling and Psychotherapy Association (CCPA) to respond: 511 (22.9%) completed surveys were returned. Survey data indicate that CCPA members do not believe that the professional identity among Canadian counsellors is clear and coherent and they do not perceive that the profession is widely respected among the public for the services it provides. However, respondents expressed a very high degree of satisfaction with their career decision to become counsellors. The findings have implications for counsellor education as well as the practice of counselling in Canada.